Mercury Dynamics in Mining-Adjacent Ecosystems: Risk Assessment of Lake Lais, Central Kalimantan, Indonesia - Rosana Elvince; Budhi Ardhani (BRIN Publishing, 2025)
Mercury is a hazardous chemical that significantly impacts both the environment and human health. In Central Kalimantan, gold mining activities contribute to mercury contamination, particularly in aquatic ecosystems. Lake Lais, an oxbow lake along the Kahayan River, is potentially affected by mercury from upstream mining activities. This study aims to assess mercury contamination in Lake Lais water and sediment, and evaluate the ecological risks associated with mercury pollution. In September 2024, water and sediment samples were collected from five sites in Lais Lake. Water samples were collected from the surface using polypropylene bottles with added nitric acid to preserve mercury content. Sediment samples were taken using an Ekman grab and analyzed for mercury using Atomic Absorption Spectrophotometry (AAS) at Balai Standarisasi Pelayanan Jasa Industri in Banjarbaru, South Kalimantan. The results showed that water mercury concentrations ranged from 0.00 to 0.002 mg/l, which is within the limits set by the Indonesian government (PP No. 22/2021). However, sediment mercury levels ranged from 0.14 to 0.47 mg/kg, which can negatively impact the ecosystem based on international standards. Lais Lake was classified as having mild to moderate mercury contamination, with an ecological risk ranging from moderate to very strong. The Risk Quotient (RQ) exceeded 1, indicating high ecological risk. These findings highlight the need for regular monitoring and stricter regulation of mercury use in mining. Future research should focus on long-term impacts and seasonal variations in mercury levels to better assess ecological risks.